The Common Law in Two Voices : Language, Law, and the Postcolonial Dilemma in Hong Kong. - Ng, Kwai Hang (Stanford University Press, 2009)
This book examines how language changes the way law is debated and negotiated, focusing on the courtrooms of postcolonial Hong Kong.